Reform of Islamic Inheritance Law and its Role in the Formation of National Inheritance Law - Djamud, Hikmatullah; Tarihoran, Naf'an; Ma'rifa, Nurul; Fauzan, Abdul; Aniyatussaidah, Aniyatussaidah (Jurnal Hukum Ekonomi Syariah, 2025)
This study examines the reform of Islamic inheritance law and its role in the formation of a national inheritance law that is more just, inclusive and adaptive to social change. Using the literature research method, this study examines the principles of Islamic inheritance law and its contribution to the national legal system. The results show that the reform of Islamic inheritance law is an important part of the development of national inheritance law, with a major role in improving social justice, legal certainty, and accommodation to the diversity of society. This reform is realized through several strategies, namely: (1) increasing gender equality in the distribution of inheritance, (2) harmonizing Islamic inheritance law with civil law, (3) adjusting the principles of inheritance distribution to be more relevant to the social context, and (4) applying the concept of mandatory will to protect the rights of certain heirs. This research confirms that Islamic inheritance law reform not only plays a role in strengthening the national legal system, but also becomes a strategic element in creating a more cohesive, responsive, and just inheritance law.